Application of Multiple Intelligence in Aqidah Moral Subjects at SMA Negeri 1 Jakarta - Annisa Nur Fadhilah; Totong Heri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
As we know, the application of the Multiple Intelligence theory in the world of education has been widely researched before, and the majority shows good results and the theory is very useful if it can be adopted in the school learning system. As quoted in an international journal with the title